Compartment-specific adaptive responses and dysregulation under NQO1 deficiency in diabetic kidney disease: A transcriptomic GSEA-based investigation - Yongwoo Lee; Sang-Hee Lee; Eunyoung Moon; Hyerim Park; Janghyun Jo; Jung Hwan Hwang; Dae Eun Choi (PLoS ONE, 2025)
Diabetic kidney disease (DKD) involves oxidative stress–driven damage to glomeruli (Gloms) and proximal convoluted tubules (PCT). NAD(P)H: quinone oxidoreductase 1 (NQO1) regulates redox balance, but its compartment-specific role remains unclear. Streptozotocin (STZ)-induced hyperglycemia increased albuminuria and foot process effacement, with NQO1 KO (NKO) mice exhibiting greater podocyte injury than WT, indicating exacerbated glomerular damage. To investigate the underlying mechanisms, we conducted compartment-specific transcriptomic Gene Set Enrichment Analysis (GSEA) in Gloms and PCT. In Gloms, ribosome biogenesis and immune pathways were upregulated in WT-STZ compared to WT but suppressed in NKO-STZ compared to STZ, indicating impaired protein synthesis and immune regulation in NQO1 deficiency. In PCT, ribosome activity, oxidative phosphorylation, glutathione metabolism, and cytoskeletal pathways were elevated in WT-STZ compared to WT but suppressed in NKO-STZ compared to WT-STZ. However, ribosome activity was relatively less affected than in Gloms. Additionally, adherens junction activation was more pronounced in WT-STZ Gloms than in NKO mice Gloms, suggesting a compensatory mechanism to maintain podocyte foot process integrity. This response involved key cytoskeletal genes, including Actg1, Ctnna1, Tjp1, Rhoa, and Iqgap1. These findings highlight compartment-specific adaptive responses to STZ-induced hyperglycemia and underscore NQO1’s role in regulating these adaptations. Our results suggest that enhancing NQO1 activity may restore redox balance and preserve nephron integrity, supporting its potential as a therapeutic target for DKD. Furthermore, the observed compartment-specific responses highlight the need for precision redox therapies tailored to glomerular and tubular vulnerabilities.